ANALYSIS AND DESIGN OF MULTI-USER SYSTEM ABC - Karwan Ngadi; Ir. Oon Amrozi, Msc (Jurnal Sistem Informasi, 1994)
Personal Computer (PC) at the current rapid development. Not only used for private purposes but also for business. To meet the needs of data communications, and now PCs can be linked in a network (network) are integrated in a limited location, called Local Area Networks (LAN). The concept of multi-user system is used by banks in the process of saving the ABC. But whether multi-user LAN system has many advantages compared with the mini machine? Authors in this study tried to owned by the Local Area Network (LAN). The author conducted research in several stages, library research, data collection, data processing and analysis of research.